Kontribusi Kreativitas Dan Disiplin Belajar Terhadap Prestasi Belajar Pada Materi Bunyi Siswa Kelas VIII SMP N 1 Gatak Tahun Ajaran 2016/2017 - Kurniawan, Andri, Dr. Sofyan Anif, M.Si (2017)
The purpose of this study are: 1) To know the contribution of learning creativity to learning achievement on sound material; 2) To know the contribution of learning discipline to the learning pretation in sound material; 3) To know the contribution of learning creativity and learning discipline together to the learning achievement in sound material. This type of research is descriptive quantitative. This research took the research location at SMP Negeri 1 Gatak. The population in this study can be clearly identified, because the nature and identity of the respondents is detected by the university management. The sample was taken as many as 75 students, with data collection techniques using ionnaires and documentation techniques. Data analysis techniques used to test the hypothesis is multiple linear regression lysis, t test and F test, in addition to the calculation of coefficient of determination, relative donation and effective contribution. The results of this study are 1) There is a significant influence in the contribution of learning creativity to learning achievement. This can be seen from the result of double linear regression analysis (t test) because tcount>ttable, that is 6,569> 1,993 and significance value <0,05, that is 0.000. With effective contribution of 62.057%; 2) There is no significant influence in the contribution of learning discipline to learning achievement. The result of double linear regression analysis obtained because t count <t table, that is -0.113 <1,983 and significance value <0,05, that is 0,910 with effective contribution equal to -0,0,98%; 3) There is a significant influence between the contribution of learning creativity and learning discipline affect the students' achievement of SMP Negeri 1 Gatak academic year 2016/2017. This can be seen from the analysis of F test that obtained Fcount>Ftable, that is 21,749> 3,124 and significance value <0,05, that is 0.000. With the results of determination coefficient test (R2) of 0.614 indicates that the magnitude of the influence of learning creativity and learning discipline affect the student achievement of SMP Negeri 1 Gatak academic year 2016/2017.